On charge effects to the electromagnetism-like algorithm - Rocha, Ana Maria A. C. (2008)
This paper presents modifications of the electromagnetism-like (EM) algorithm for solving global optimization problems with box constraints. The modifications are concerned with the charges associated with each point in the population. The purpose here is to improve efficiency and solution accuracy by exploring the attraction-repulsion mechanism of the EM algorithm. Several widely used benchmark problems were solved in a performance evaluation of the new algorithm when compared with the original one. The modified algorithm has also been compared with other heuristic population-based methods.